Penilaian Kinerja Kelembagaan Koperasi Desa Merah Putih berbasis Multi-Dimensi untuk Mewujudkan Tata Kelola Koperasi Modern - Sukaris Sukaris; Suwandi Suwandi; Hernum Daya Wati; Suwarno Suwarno; Endah Mulyani (Jurnal Simki Economic, 2026)
This study aims to analyze the institutional performance of the Koperasi Desa Merah Putih (KDMP), identify factors influencing its performance, and formulate implications for institutional strengthening towards modern cooperative governance. The study uses a descriptive-evaluative approach. Data were collected through a multi-dimensional survey of six institutional aspects supplemented by in-depth interviews, observations, and documentation studies, then analyzed descriptively using quantitative and thematic qualitative methods. The results indicate that KDMP has a strong formal institutional foundation, including legality, organizational structure, and standard operating procedures. However, weaknesses remain in the aspects of services, infrastructure, human resource capacity, and economic impact on members. The novelty of this study lies in the multi-dimensional approach to institutional performance assessment integrated with the principles of modern cooperative governance. Theoretically, this study shows that formal institutional readiness is not necessarily directly proportional to the operational performance and economic impact of the cooperative.